The Concept of Facilities and Infrastructure Management in Schools: A Literature Review - Nurhuda, Abid; Fajri, Muhammad Al; Rahman, Ts Engku Shahrulerizal bin Engku Ab (IJECA (International Journal of Education and Curriculum Application), 2023)
Education is a long-term investment in human resources and aims to produce quality generations. One way to guarantee the achievement of this goal is to require standards for facilities and infrastructure that schools must have and how to manage this, because there are still many schools that don't know about it, plus there are inadequate facilities, which creates a quality gap between schools themselves. So this research aims to describe the concept of management of facilities and infrastructure in schools. The method used is a literature study with a descriptive qualitative approach, then the relevant content is analyzed and conclusions are drawn. The results of the research show that the concept of infrastructure management in schools includes 3 important things, namely the planning concept, then the procurement concept which consists of purchasing, self-manufacturing, renting, borrowing, receiving grants, exchanging, recycling, and repairing, finally the regulatory concept which consists of inventory, storage, maintenance, and use. The hope is that these concepts can optimize the educational process and make learning in schools more effective and efficient.